2021
DOI: 10.1080/07853890.2021.1961015
|View full text |Cite
|
Sign up to set email alerts
|

Spectral domain-optical coherence tomography retinal biomarkers in choroidal neovascularization of multifocal choroiditis, myopic choroidal neovascularization, and idiopathic choroidal neovascularization

Abstract: Objective: To use optical coherence tomography (OCT) to compare retinal biomarkers of choroidal neovascularization (CNV) secondary to multifocal choroiditis (MFC), myopic choroidal neovascularization (mCNV), and idiopathic choroidal neovascularization (ICNV) and to provide a basis for its clinical diagnosis and treatment. Methods: In this retrospective case study, patients admitted to the Second Hospital of Hebei Medical University between January 2018 and January 2021 who were initially diagnosed with CNV sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…OCTA visualizes vasculature by detecting motion contrast of moving blood cells and can even evaluate subclinical alterations in CC ( 29 , 30 ). Figure 3, A–C , shows a comparison between ICGA imaging ( Figure 3, A and B ) and CC segmented OCTA ( Figure 3C ) of the same retinal region, revealing higher resolution of OCTA.…”
Section: Resultsmentioning
confidence: 99%
“…OCTA visualizes vasculature by detecting motion contrast of moving blood cells and can even evaluate subclinical alterations in CC ( 29 , 30 ). Figure 3, A–C , shows a comparison between ICGA imaging ( Figure 3, A and B ) and CC segmented OCTA ( Figure 3C ) of the same retinal region, revealing higher resolution of OCTA.…”
Section: Resultsmentioning
confidence: 99%
“…1 Gao et al confirmed this pathogenetic relationship, showing that pitchfork sign was present in 40% of patients with MFC. 12 Over time, De Mello et al first reported in 2015, 13 followed by Rajabian et al in 2019, 2 demonstrated the presence of the pitchfork sign associated with choroidal osteoma. In these patients, focal choroidal excavation developed at the level of the ossifying tumor, resulting in CNV with associated hyperreflective finger-like projections.…”
Section: Discussionmentioning
confidence: 99%
“…Gao et al confirmed this pathogenetic relationship, showing that pitchfork sign was present in 40% of patients with MFC. 12…”
Section: Discussionmentioning
confidence: 99%
“…Anatomic studies demonstrate that choroid plays a crucial role in supporting photoreceptor function; such atrophy may have significant deleterious impact on outer retina and RPE health. Previous studies have put forth the theory that alterations in the choroidal blood perfusion may lead to degenerative changes in pathological myopia and high myopia ( 2 ). Narrowing and loss of large choroidal vessels, and occlusion of choriocapillaris, have been suggested to be important in the pathogenesis of chorioretinal atrophy in pathological myopia ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Myopia is one of the most common ocular disease globally, with a prevalence of 10-30% in the adult population and 80-90% in young adults in East and Southeast Asia (1). Pathological myopia is one of the leading causes of visual impairment in the world, in which excessive axial elongation of the globe causes biomechanical stretching and thinning of choroid and retinal pigmented epithelium (RPE) layers (2)(3)(4), leading to increased risk of chorioretinal complications such as myopic choroidal neovascularization (mCNV), posterior staphyloma, lacquer cracks, and myopic foveoschisis, among which mCNV is considered to be sight-threatening with poor prognosis without treatment (5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%